Factors Related to HIV/AIDS Risk Behavior in Ship Crew at Tenau Kupang Port - Dere, Neltji Marsalina; Weraman, Pius; Manurung, Imelda FE; Syamruth, Yendris K; Wahyuni, MM Dwi (Indonesian Journal of Medicine, 2025)
Background: In 2022, East Nusa Tenggara recorded the highest number of HIV-AIDS cases in the province, with a total of 151 patients. HIV-AIDS infections are spread across six districts: Oebobo (27.8%), Maulafa (18.5%), Kelapa Lima (22.5%), Alak (16.5%), Kota Lama (4.6%), and Kota Raja (10%). HIV cases in Indonesia have fluctuated from 2019 to 2022 due to a significant percentage of high-risk behaviors exhibited by high-risk groups, including ship crew members. This study aims to analyze the factors related to HIV/AIDS risk behaviors in ship crew members. Subjects and Method: This was a cross-sectional study conducted at Tenau Port, Kupang, East Nusa Tenggara, Indonesia from November to December 2024. The study population consists of all crew members (ABK) on domestic cargo ships arriving and docking at Tenau Kupang Port in 2024, estimated to be 225 ABK. A simple random sampling technique was used, with 96 samples selected based on the Lemeshow formula. Data were collected using a questionnaire. Results: The chi-square test results revealed a significant relationship between knowledge (p = 0.029; OR = 2.734; 95% CI: 1.188–6.296), ship docking duration (p = 0.014; OR = 3.215; 95% CI: 1.342–7.702), and peer support (p = 0.000; OR = 27.586; 95% CI: 3.476–218.930) with HIV/AIDS risk behavior. Attitude (p = 0.272; OR = 0.455; 95% CI: 0.145–1.427), education (p = 1.000; OR = 1.136; 95% CI: 0.089–18.711), income (p = 0.587; OR = 0.587; 95% CI: 0.516–5.093), frequency of going home (p = 0.657; OR = 0.753; 95% CI: 0.324–1.752), and marital status (p = 1.000; OR = 0.948; 95% CI: 0.424–2.127) showed no significant relationship. It is necessary to increase socialization to raise awareness of HIV/AIDS prevention among ABK members and foster positive social support within the crew. Conclusion: There is a need to increase knowledge about the risks of HIV/AIDS through outreach and counseling.